FUNCTIONING OF ADMINISTRATIVE JUDICIARY IN THE CONDITIONS OF MARTYR STATE IN UKRAINE - Netska, Liubov; Yakymenko, Pavlo (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: a comprehensive analysis of the regulatory, organizational and procedural transformations of administrative justice in Ukraine under martial law in order to identify key problems and prospects for improving this type of justice. Research methods: dialectical, systemic-functional, analysis and synthesis, formal-legal, logical-legal. Results: key problems of administrative justice under martial law are outlined. Changes in procedural legislation aimed at overcoming the challenges facing administrative courts are analyzed. The effectiveness of the implemented digital tools and their impact on access to justice and ensuring the continuity of the administrative judicial process are assessed. Proposals are made to improve legislation, administrative judicial proceedings, and judicial practice in certain categories of disputes. Discussion: the impact of martial law and legal regulation on the organization and implementation of administrative justice. Legislative grounds for remote trial. Good reasons for administrative courts to resume procedural deadlines established by law under martial law. Administrative disputes about restrictions on the rights and freedoms of citizens under martial law. Improving the digitalization of administrative proceedings, taking into account modern risks and technical inaccessibility for certain groups of citizens. Administrative justice during martial law demonstrated resilience and the ability to administer justice. The introduction of digital technologies contributed to positive changes and transformation of the judicial system. Gradual improvement of administrative procedural legislation based on practical requests continues. The most important task for administrative justice during the period of restriction of constitutional rights is to ensure a balance between the protection of national security and the preservation of fundamental human rights and freedoms. The court should act not only as an arbitrator in disputes, but also as a guarantor that even in conditions of extraordinary challenges, the law remains effective and the state does not lose its democratic face.